Generating virtual images from oblique frames - Tommaselli, Antonio M.G. [UNESP]; Galo, Mauricio [UNESP]; De Moraes, Marcus V.A. [UNESP]; Marcato Jr., José [UNESP]; Caldeira, Carlos R.T. [UNESP]; Lopes, Rodrigo F. (MDPI, 2013)
Image acquisition systems based on multi-head arrangement of digital camerasare attractive alternatives enabling a larger imaging area when compared to a single framecamera. The calibration of this kind of system can be performed in several steps or byusing simultaneous bundle adjustment with relative orientation stability constraints. Thepaper will address the details of the steps of the proposed approach for system calibration,image rectification, registration and fusion. Experiments with terrestrial and aerial imagesacquired with two Fuji FinePix S3Pro cameras were performed. The experiments focusedon the assessment of the results of self-calibrating bundle adjustment with and withoutrelative orientation constraints and the effects to the registration and fusion when generatingvirtual images. The experiments have shown that the images can be accurately rectified andregistered with the proposed approach, achieving residuals smaller than one pixel. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Camera calibration; Dual head; Fusion of multiple images; Photogrammetry; Dual-head; Image acquisition systems; Image rectification; Multiple image; Orientation constraint; Relative orientation; System calibration; Calibration; Cameras; Experiments; Image fusion